Magnetic Quantum Dots: Synthesis, Spectroscopy, and Magnetism of Co2+- and Ni2+-Doped ZnO Nanocrystals - Schwartz, Dana A; Norberg, Nick S; Nguyen, Quyen P; Parker, Jason M; Gamelin, Daniel R (Journal of the American Chemical Society, 2003)
We report a method for the preparation of colloidal ZnO-diluted magnetic semiconductor quantum dots (DMS-QDs) by alkaline-activated hydrolysis and condensation of zinc acetate solutions in dimethyl sulfoxide (DMSO). Mechanistic studies reveal that Co2+ and Ni2+ dopants inhibit nucleation and growth of ZnO nanocrystals. In particular, dopants are quantitatively excluded from the critical nuclei but are incorporated nearly isotropically during subsequent growth of the nanocrystals. The smaller nanocrystal diameters that result upon doping are explained by the Gibbs−Thompson relationship between lattice strain and crystal solubility. We describe methods for cleaning the nanocrystal surfaces of exposed dopants and for redispersion of the final DMS-QDs. Homogeneous substitutional doping is verified by high-resolution low-temperature electronic absorption and magnetic circular dichroism (MCD) spectroscopies. A “giant Zeeman effect” is observed in the band gap transition of Co2+:ZnO DMS-QDs. MCD and Zeeman spectroscopies are used to quantify the magnitude of the p−d exchange interaction (N 0β) that gives rise to this effect. N 0β values of −2.3 ± 0.3 eV (−18 500 cm-1) for Co2+:ZnO and −4.5 ± 0.6 eV (−36 300 cm-1) for Ni2+:ZnO have been determined. Ligand-to-metal charge-transfer transitions are observed in the MCD spectra of both Co2+:ZnO and Ni2+:ZnO DMS-QDs and are analyzed in the context of an optical electronegativity model. The importance of these charge-transfer states in determining N 0β is discussed. Ferromagnetism with T C > 350 K is observed in aggregated nanocrystals of Co2+:ZnO that unambiguously demonstrates the existence of intrinsic high-T C ferromagnetism in this class of DMSs.